Ocular Surface Diseases Some Current Date on Tear Film Problem and Keratoconic Diagnosis - Kopacz, Dorota (IntechOpen, 2021)
The ocular surface refers to the cornea, conjunctiva, lacrimal glands, and lid of the eye. It is composed of the mucosa that lines the globe and palpebrae, the corneoscleral limbus, the corneal epithelium, and the tear film. This book focuses on the tear film, describing its physiology, dynamics, and role in maintaining the health of the ocular surface. It also examines keratoconus, a condition affecting both the preocular tear film and the ocular surface in which the cornea thins and bulges outward, as well as recent possibilities in molecular genetics.